2022
DOI: 10.1136/jitc-2021-003392
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab and decitabine for refractory or relapsed acute myeloid leukemia

Abstract: BackgroundThe powerful ‘graft versus leukemia’ effect thought partly responsible for the therapeutic effect of allogeneic hematopoietic cell transplantation in acute myeloid leukemia (AML) provides rationale for investigation of immune-based therapies in this high-risk blood cancer. There is considerable preclinical evidence for potential synergy between PD-1 immune checkpoint blockade and the hypomethylating agents already commonly used for this disease.MethodsWe report here the results of 17 H-0026 (PD-AML, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 80 publications
3
31
0
Order By: Relevance
“…In line with the previous study, responses were observed in six patients; one achieved a morphologic leukemia-free state, three with stable disease, and two achieved CR [ 43 ]. The combination was found to be safe with a median OS of 10 months [ 43 ].…”
Section: Pd-1/pdl-1 Blockadesupporting
confidence: 87%
See 2 more Smart Citations
“…In line with the previous study, responses were observed in six patients; one achieved a morphologic leukemia-free state, three with stable disease, and two achieved CR [ 43 ]. The combination was found to be safe with a median OS of 10 months [ 43 ].…”
Section: Pd-1/pdl-1 Blockadesupporting
confidence: 87%
“…The combination was well tolerated and particularly active in the newly diagnosed setting [ 42 ]. In another study conducted by Goswami et al, pembrolizumab plus 10 days of decitabine was tested in 10 patients with R/R AML [ 43 ]. In line with the previous study, responses were observed in six patients; one achieved a morphologic leukemia-free state, three with stable disease, and two achieved CR [ 43 ].…”
Section: Pd-1/pdl-1 Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…4), the few studies performed so far with anti-PD-L1 antibodies in AML patients have shown only modest clinical activity. Their impact has been evaluated also in combination with hypomethylating agents [132][133][134], since they induce the expression of several immune-related genes, including HLA-I and HLA-II, leukemia-associated antigens (e.g., PRAME, WT1) [135], PD-1 and PD-L1 [136]. Despite most studies did not specifically evaluate NPM1-mutated AML, they showed that patients who might benefit more from these drug combinations are those who are naïve for hypomethylating agents or have <20% blasts and a higher pretherapy infiltration of bone marrow by CD3+, CD4+ Teff, and CD8+ T cells [132].…”
Section: Antibodies Against Cd33 and Cd123mentioning
confidence: 99%
“…A clinical trial combining the PD-1 inhibitor nivolumab with the hypomethylating agent azacitidine, performed against this background, showed remarkable efficacy; the ORR was 58% in HMA–naïve patients [ 154 ]. Recent clinical trials combining immune checkpoint inhibitors and conventional drugs for the treatment of AML and/or MDS are summarized in Table 4 [ 155 , 156 , 157 , 158 ].…”
Section: Icismentioning
confidence: 99%